Panic at the disco: solar-powered strobe light barriers reduce field incursion by African elephants Loxodonta africana in Chobe District, Botswana. Issue 5 (3rd September 2021) - Adams, Tempe S. F.; Mwezi, Isaiah; Jordan, Neil R.
Abstract: Managing interactions between humans and wild elephants is a complex problem that is increasing as a result of agricultural and urban expansion into and alongside protected areas. Mitigating negative interactions requires the development of new tools to reduce competition and promote coexistence. Many studies have tested various mitigation techniques across elephant ranges in Africa and Asia, with varying levels of success. Recently, strobe lights have been suggested as a potential mitigation strategy in deterring African lions Panthera leo from kraals or bomas, but this technique has to date not been tested to reduce negative human–elephant interactions. Over a 2-year period (November 2016–June 2018), we tested the effectiveness of solar-powered strobe light barriers in deterring African elephants Loxodonta africana, in collaboration with 18 farmers in a community adjacent to the Chobe Forest Reserve and Chobe National Park in northern Botswana. Although elephants were more likely to pass by fields with solar-powered strobe light barriers (which was probably a result of selection bias as we focused on fields that had previously been damaged by elephants), they were less likely to enter these treatment fields than control fields without such barriers. Our findings demonstrate the efficacy of light barriers to reduce negative human–elephant interactions in rural communities.